2015
DOI: 10.2138/am-2015-5095
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure compressibility and phase stability of Mn-dolomite (kutnohorite)

Abstract: We measured the bulk modulus and phase stability of a natural Mn-dolomite, kutnohorite, to 19 GPa. At room temperature, kutnohorite is stable in the rhombohedral dolomite phase up to 19 GPa, with an isothermal bulk modulus of 85(6) GPa (Kʹ = 4). The compressibility of kutnohorite is found to match well with both single and double carbonate trends with respect to bulk modulus and unit-cell volume. The thermoelastic properties measured in this study show that the Mn dolomite end-member fits well with the systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The phase transition pressures of BaMg(CO 3 ) 2 , BaFe(CO 3 ) 2 , and BaMn(CO 3 ) 2 are 2.4(2), 2.7(5), and 3.9(2) GPa in this study, respectively. Compared with this study and previous results (Lin et al 2012;Spivak et al 2014;Cerantola et al 2015;Merlini et al 2015;Palaich et al 2015;Fu et al 2017;Merlini et al 2017;Vennari and Williams 2018;Binck et al 2020;Chariton et al 2020;Wang et al 2022), the phase stability of norsethite-type Ba(Mg,Fe,Mn)(CO 3 ) 2 , dolomite-type Ca(Mg,Fe,Mn)(CO 3 ) 2 , and calcite-type (Mg,Fe,Mn)CO 3 carbonates at ambient temperature were presented in Figure 7. The effective cation radii of Ba 2+ , Ca 2+ , Mn 2+ , Fe 2+ , and Mg 2+ are 1.35, 1.00, 0.83, 0.78, and 0.72 Å at ambient conditions, respectively (Shannon and Prewitt 1969).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The phase transition pressures of BaMg(CO 3 ) 2 , BaFe(CO 3 ) 2 , and BaMn(CO 3 ) 2 are 2.4(2), 2.7(5), and 3.9(2) GPa in this study, respectively. Compared with this study and previous results (Lin et al 2012;Spivak et al 2014;Cerantola et al 2015;Merlini et al 2015;Palaich et al 2015;Fu et al 2017;Merlini et al 2017;Vennari and Williams 2018;Binck et al 2020;Chariton et al 2020;Wang et al 2022), the phase stability of norsethite-type Ba(Mg,Fe,Mn)(CO 3 ) 2 , dolomite-type Ca(Mg,Fe,Mn)(CO 3 ) 2 , and calcite-type (Mg,Fe,Mn)CO 3 carbonates at ambient temperature were presented in Figure 7. The effective cation radii of Ba 2+ , Ca 2+ , Mn 2+ , Fe 2+ , and Mg 2+ are 1.35, 1.00, 0.83, 0.78, and 0.72 Å at ambient conditions, respectively (Shannon and Prewitt 1969).…”
Section: Discussionsupporting
confidence: 66%
“…Compared to the norsethite-type family BaMg(CO 3 ) 2 , the K 0 of α-BaFe(CO 3 ) 2 is distinctly smaller than that of α-BaMg(CO 3 ) 2 (K 0 = 66.2 GPa) (Pippinger et al 2014). Different from the comparable K 0 values of dolomite-type carbonates, the K 0 values are 95(1), 92(1), and 85(6) for CaMg(CO 3 ) 2 , CaMg 0.6 Fe 0.4 (CO 3 ) 2 , and Ca 0.76 Mn 1.24 (CO 3 ) 2 , respectively (K 0 ′= 4) (Merlini et al 2017;Palaich et al 2015). It may be attributed to the existence of superlattice in α-BaMg(CO 3 ) 2 , which greatly improves its incompressibility (Helmersson et al 1987;Pippinger et al 2014;Dong et al 2015).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…(Binck et al, 2020b), it is denoted as the Dol-Ⅱ phase in this study. Moreover, Palaich et al (2015) reported a dramatic increase in the volume of Mn-rich dolomite sample Ca 0.76 Mn 0.1.24 (CO 3 ) 2 in a neon PTM at 15.9 GPa, associated with the disappearing and splitting of several diffraction lines in the powder x-ray diffraction (XRD) patterns. To some extent, this result supports the phase transition of Mn-dolomite revealed in the high-pressure evolution of Raman spectra in this study.…”
Section: Resultsmentioning
confidence: 99%